Productivity of tax offices in Norway - Finn R. Førsund; Dag Fjeld Edvardsen; Sverre A. C. Kittelsen; Frode Lindseth (University of Oslo, Department of Economics, 2009)
The performance of local tax offices of Norway is studied over a three-year period using Data Envelopment Efficiency analysis and calculating Malmquist productivity indices. One input, labour, is used, and six output categories of the main service activities carried out by tax offices are specified. A bootstrap approach recently developed for DEA models is applied to establish confidence intervals for the individual indices enabling an identification of units that have either significant productivity decline or growth, or no change. A specially developed graphic display gives a visual test and grouping into the three possible categories. Looking at change in labour use and productivity change together the productivity development of individual offices is classified into the four categories efficient labour increase, efficient labour savings, inefficient labour savings and inefficient labour increase.
Keywords: C60; D24; L89; 330; Tax office; Malmquist productivity index; DEA; bootstrap; Finanzverwaltung; Gemeinde; Data-Envelopment-Analyse; Bootstrap-Verfahren; Norwegen